DAMPAK EKOWISATA AIR TERJUN HOKO TERHADAP KONDISI SOSIAL BUDAYA DAN EKONOMI MASYARAKAT DI DESA HOKO KECAMATAN KEI BESAR UTARA TIMUR KABUPATEN MALUKU TENGGARA - Yoan Avicenia Putri Silubun; Henderina Lelloltery; Billy B. Seipala (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to determine the impact of Hoko Waterfall ecotourism activities on the economic and socio-cultural conditions of the community in Hoko Village, Kei Besar Utara Timur District, Southeast Maluku Regency. The research employed qualitative and quantitative approaches through observation, interviews, and documentation involving 40 respondents consisting of local residents, tourism managers, and traditional leaders. The results show that, economically, ecotourism has generated significant positive effects on community income. The Travel Cost Method (TCM) analysis indicates that the average visitor expenditure reaches IDR 400,000 per person, most of which benefits local businesses such as transportation providers, food vendors, and tourism service operators. Ecotourism activities have created new employment opportunities and encouraged livelihood diversification from fisheries and agriculture to tourism services. From the socio-cultural perspective, ecotourism has not diminished traditional values rooted in the Larvul Ngabal customary law, caste system (Mel, Ren, Iri), and rituals such as Sasi darat and Sasi laut, which remain preserved in their sacred forms. The Kei language continues to be maintained as a cultural identity, and the spirit of mutual cooperation (maren) remains strong. Thus, Hoko Waterfall ecotourism contributes to improving the community’s economic welfare while reinforcing their cultural identity amidst modernization.